Whole-Brain Mapping the Direct Inputs of Dorsal and Ventral CA1 Projection Neurons - Tao, Sijue; Wang, Yihang; Peng, Jundan; Zhao, Yang; He, Xiaobin; Yu, Xuefeng; Liu, Qing; Jin, Sen; Xu, Fuqiang (Frontiers in Neural Circuits, 2021)
The CA1, an important subregion of the hippocampus, is anatomically and functionally heterogeneous in the dorsal and ventral hippocampus. Here, to dissect the distinctions between the dorsal and ventral CA1 (dCA1 and vCA1) in anatomical connections, we systematically analyzed the direct inputs to dCA1 and vCA1 projection neurons (PNs) with the rabies virus-mediated retrograde trans-monosynaptic tracing system in Thy1-Cre mice. Our mapping results revealed that the input proportions and distributions of dCA1 and vCA1 varied significantly. Inside hippocampal formation, dCA1 and vCA1 PNs shared the same upstream brain regions, but with distinctive distribution patterns along the rostrocaudal axis. The intrahippocampal inputs to the dCA1 and vCA1 exhibited opposite trends, decreasing and increasing gradually along the dorsoventral axis, respectively. For extrahippocampal inputs, dCA1 and vCA1 shared some monosynaptic projections from certain regions such as pallidum, striatum, hypothalamus, and thalamus. However, vCA1, not dCA1, received innervations from the subregions of olfactory areas and amygdala nuclei. Characterization of the direct input networks of dCA1 and vCA1 PNs may provide a structural basis to understand the differential functions of dCA1 and vCA1.